The business environment : a global perspective - Worthington, Ian, 1946- (Pearson, 2018)
"In an uncertain economic environment with fast-paced changing cultures and contexts, today's organizations can seem a tricky and complex world to understand. The Business Environment - A Global Perspective endows students with a toolset for identifying, analysing and planning for external (PESTLE) and internal factors in business strategy. This book is about all of us and the world we and businesses live in, because organizations do not exist in a vacuum. Now in its eighth edition this text gives students the fundamental knowledge of how domestic and international business environments operate in a systematic and logical approach. The Business Environment takes the reader through contexts, types of organization and markets, dealing with contemporary issues in socioeconomic, political and legal structures. · Clear explanations of economics such as why the prices of things we buy might go up or down, or why at any given time it might be harder or easier to get a job. · Put theory into practice with a wealth of case studies from a diverse range of local and international organizations such as Facebook, GSK and JCB building into more detailed International Business in Action part case studies providing real life data to analyse on e.g. Quantitative Easing and the global financial crisis. End of chapter review and discussion questions along with assignments - to test both your knowledge and understanding and how to apply the concepts in real life, and new - Brexit, contexts"--